THE MEANING OF ISLAMIC ARCHITECTURE IN THE AR RAHMAN MOSQUE, BLITAR CITY AS A MEDIA FOR DAKWAH AND EDUCATION - chosinawarotin, chosinawarotin; Bambang, Hardadi; Ade Virra , Maretta (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2024)
Mosques are holy places for Muslims used for worship and other religious activities. The Ar-Rahman Mosque in Blitar City, which was inaugurated in 2019, not only functions as a place of worship, but also as a center for Islamic education and preaching. With architecture that resembles the Prophet's Mosque in Medina, this mosque conveys deep spiritual and symbolic messages through its design elements. This research aims to examine the meaning of the architecture of the Ar-Rahman Mosque in the context of Islamic da'wah and education and its influence on the spiritual experience of the congregation. Adopting a qualitative approach, data was collected through surveys, direct observation, and interviews with mosque managers, religious leaders, and local communities. The research results show that the architecture of the Ar-Rahman Mosque has a significant impact in enriching the spiritual experience of the congregation. Elements such as umbrella-like poles, calligraphic carvings, and the use of symbolic colors play an important role in conveying Islamic messages and educational values. The harmonious interior and exterior design creates a solemn and calm atmosphere, supporting worship and spiritual reflection. Through this research, it is hoped that it can contribute to religious and architectural literature and strengthen the role of mosques as centers of da'wah and education in local communities. The Ar-Rahman Mosque, with its combination of the beauty of Islamic architectural art and its comprehensive function, serves as an important cultural and spiritual heritage for the community in Blitar City. Keywords: Education, Architecture, Mosque, Ar-Rahman, Da'wah